Xenophobic attitudes in German police officers: A longitudinal investigation from professional education to practice - Krott, Nora Rebekka (International journal of police science & management, 2018)
In recent years, the proportion of the population with a migrant background has increased in the Federal Republic of Germany. We investigated whether young German police officers hold xenophobic attitudes at the beginning of their bachelor studies and how intercultural competence and communication training modules affect the development of those attitudes. In a 4-year longitudinal study, we assessed police officers’ xenophobic attitudes at the beginning of the first academic year, after basic study (year 1), after main study (year 2), and within the first year of professional practice (year 4). There was a significant decrease in xenophobic attitudes within the 3 years of professional education, followed by a slight increase within the first year of professional practice. Throughout the 4-year period, xenophobic attitudes decreased significantly, pointing to the effectiveness of the training modules integrated into the bachelor program and to the necessity to continue intercultural training within police departments.